Portable wrapping machine / Muhammad Hakim Hisam - Hisam, Muhammad Hakim (2023)
This project is presenting a portable wrapping machine that has been improvised by adding new feature such as make it portable that is easy to operate and it is user friendly. The Objective of this machine is to increase the production rate for home sellers and ease their job. The design of the machine is fit for small cylinder or box within the machine size. A motor has been installed in the to wrap the object. There is a power supply that will covert ac current to dc current to supply electricity to the motor. The potential in commercial the portable bubble wrapping machine is very high because portable wrapping machine in the current market is not well establish